HUBUNGAN LINGKAR PINGGANG DENGAN PROFIL LIPID PADA PASIEN DIABETES MELITUS TIPE 2 - Simbar, Mentari; Pandelaki, Karel; Wongkar, M. C.P (e-CliniC, 2015)
Abstract: Waist circumference is often used to evaluate abdominal fat mass. Waist circumference is correlated with abdominal mass and is a predictor of type 2 diabetes mellitus compared to BMI. Diabetes Mellitus Type 2 (T2DM) is more common in individuals with overweight and obesity. T2DM is not only occured due to carbohydrate metabolism disorder of lipid metabolism but also due to dyslipidemia. Dyslipidemia caused by substances called lipoprotein VLDL (Very Low Density Lipoprotein) or triglycerides, decreased HDL cholesterol (High Density Lipoprotein) and the formation of small dense LDL (Low Density Lipoprotein) which are atherogenic. This study aimed to determine the relationship of waist circumference with the lipid profile in T2DM patients Prof. R.D. Kandou Hospital Manado. This was a descriptive cross sectional analytic study. There were 53 respondents that met the inclusion criteria. This study was conducted for three months starting from September ? November 2013 in the Endocrine Clinic. Conclusions: There was no significant correlation between waist circumference and total cholesterol, LDL, and triglycerides levels. However, there is a significant correlation between waist circumference and HDL levels.Keywords: Waist circumference, total cholesterol, HDL, LDL, Triglycerides, T2DMAbstrak: Lingkar pinggang sering digunakan sebagai penilai massa lemak abdominal, karena lingkar pinggang berkorelasi dengan massa lemak abdominal dan merupakan prediktor Diabetes Melitus Tipe 2 (DMT2) yang paling kuat dibandingkan dengan IMT. DMT2 lebih sering terjadi pada individu dengan berat badan lebih dan obesitas. Pada DMT2 bukan saja terjadi gangguan metabolisme karbohidrat melainkan juga terdapat metabolisme lipid, keadaan ini disebut dislipidemia. Dislipidemia terjadi akibat gangguan metabolisme lipoprotein yaitu Very Low Density Lipoprotein (VLDL), trigliserida, penurunan kolesterol High Density Lipoprotein (HDL), dan terbentuknya small dense Low Density Lipoprotein (LDL) yang bersifat aterogenik. Penelitian ini bertujuan untuk mengetahui hubungan lingkar pinggang dengan profil lipid pada pasien DMT2 di RSUP Prof. R.D. Kandou Manado. Jenis penelitian ini ialah deskriptif analitik dengan pendekatan cross sectional. Responden penelitian sebanyak 53 pasien yang memenuhi kriteria inklusi. Penelitian ini dilakukan selama tiga bulan yaitu dari bulan September ? November 2013 di Poliklinik Endokrin Bagian/SMF Ilmu Penyakit Dalam RSUP. Prof. R.D. Kandou Manado. Simpulan: Tidak terdapat hubungan yang bermakna antara lingkar pinggang dengan kadar kolesterol total, kadar LDL, dan trigliserida. Terdapat hubungan bermakna antara lingkar pinggang dan kadar HDL.Kata kunci: Lingkar Pinggang, Kolesterol Total, HDL, LDL, Trigliserida, DMT2